Late-Season Bermudagrass Control with Glyphosate, Fluazifop, and Mesotrione Combinations - J. Reeves; J. Hoyle; C. Thompson (Kansas Agricultural Experiment Station Research Reports, 2015)
All herbicide treatments at the Rocky Ford Research Center (RF) resulted in unacceptable control, as all plots resulted in 100% green bermudagrass cover by August 25, 2014. Any herbicide treatment combination that included glyphosate provided moderate or better control at Stagg Hill Golf Course (SH). Treatments not containing glyphosate showed no control throughout research trial.
Keywords: turfgrass; bermudagrass; bermudagrass control; glyphosate